Preparation method of compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam
By preparing compressible and tuned high-absorbent porous polyurethane electromagnetic shielding composite foam, using electrostatic self-assembly and solution blending technology, the problem that existing electromagnetic shielding materials are difficult to maintain high absorption coefficient when improving the electromagnetic shielding performance is solved, and the efficient electromagnetic shielding and absorption performance of composite foam is achieved.
Patent Information
- Application Number
- CN202510139280.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-08
AI Technical Summary
While improving the electromagnetic shielding efficiency, existing electromagnetic shielding materials are difficult to maintain a high absorption coefficient, and traditional metal materials have limited their application due to high density and chemical corrosion.
Using a compressible and tuned high-absorbent porous polyurethane electromagnetic shielded composite foam, a single layer or a small layer of MXene was obtained by etching the MAX phase precursor by lithium fluoride, and the modified nylon microspheres were electrostatically self-assembled to form MXene@PA6S particles. Combined with the thermoplastic polyurethane (TPU) skeleton and cell structure, the composite foam was prepared by solution blending and water curing.
It realizes that composite foam has both compressible tuning and high absorption coefficient, is suitable for more complex application scenarios, reduces secondary pollution, and provides a reference for the new generation of intelligent green and environmentally friendly electromagnetic shielding materials.
Smart Images

Figure HDA0005264269010000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic shielding composite materials, and in particular relates to a method for preparing a compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam. Background Art
[0002] With the development of society and the progress of science and technology, radio communication and information technology have been vigorously developed. The advent of the 5G era has further improved the efficiency of communication and transmission. The development and application of various fields such as national defense, medical care, education, and home appliances have been further improved. However, with the high-frequency operation of electronic devices and the increase in packaging density, the electromagnetic compatibility problem between electronic components has become increasingly prominent, and the accompanying electromagnetic radiation has become one of the hidden dangers to human health. Traditional electromagnetic shielding materials based on reflection loss as the dominant mechanism are generally metal materials, but their high density and easy chemical corrosion cannot be ignored. In addition, due to the skin effect of highly conductive metals, a large amount of electromagnetic waves are reflected at the material interface due to impedance mismatch, causing serious secondary pollution. This not only limits its application in electromagnetic shielding, but also poses a considerable risk to the ecological environment.
[0003] In recent years, tunable electromagnetic shielding materials have attracted widespread attention because they can be changed according to specific application and environmental requirements. Patent CN115322442A designed a temperature-responsive tunable intelligent electromagnetic shielding film. When the material is heated from room temperature to 80°C, the electromagnetic shielding effectiveness is increased from less than 20dB to more than 50dB. However, the energy consumption caused by the temperature increase and the loss of the material itself limit the practical application of the material. Liu et al. prepared a compressible tunable electromagnetic shielding effectiveness MXene aerogel, which can flexibly change within the range of 2-25dB. However, MXene aerogel is easily oxidized and is not conducive to working in a long-term environment. Polymer foams are widely used by researchers to prepare high-absorption electromagnetic shielding materials because of their porous structure, which increases the number of interfaces inside the material and causes multiple reflection losses of electromagnetic waves inside the material. Patent CN116041780A designed a multi-layer porous composite foam. With the increase of thickness, the electromagnetic shielding effectiveness increases from 23dB to 40dB. However, the absorption coefficient decreases from 0.55 to 0.15, and the contradiction between high electromagnetic shielding effectiveness and high absorption coefficient is not coordinated. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing a compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam. The polyurethane composite foam prepared by the present invention has both compressible tunability and high absorption coefficient, can be applied to more complex application scenarios, and effectively reduce secondary pollution, providing a certain reference for a new generation of intelligent green and environmentally friendly electromagnetic shielding materials.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam comprises the following steps:
[0007] (1) Etching the MAX phase precursor using lithium fluoride and concentrated hydrochloric acid to obtain a single layer or a few layers of MXene;
[0008] The specific operation is as follows: MAX phase precursor, lithium fluoride, concentrated hydrochloric acid (12 mol / L) and deionized water are mixed, stirred (500 rpm) at 30-40°C for 18-30 hours, then centrifuged at 3500 rpm for 5 minutes, washed with deionized water until the pH of the supernatant is neutral, the precipitate is collected and frozen, deionized water is added, ultrasonicated for 30 minutes under N2 atmosphere, and then centrifuged at 7000 rpm for 15 minutes, and the supernatant is freeze-dried to obtain a single layer or few layers of MXene;
[0009] The preferred MAX phase precursor is Ti3AlC2;
[0010] The molar ratio of lithium fluoride to concentrated hydrochloric acid is 1:3 to 1:3, preferably 1:3;
[0011] The freeze drying temperature is -60 to -45°C and the time is 24 to 72 hours;
[0012] (2) adding nylon microspheres (PA6S) into a polydimethyldiallylammonium chloride (PDDA) aqueous solution, stirring at room temperature for 4 to 6 hours, then centrifuging and washing, collecting the precipitate and vacuum drying to obtain PDDA@PA6S;
[0013] The particle size of nylon microspheres is 2 to 10 microns;
[0014] The mass ratio of nylon microspheres to polydimethyldiallylammonium chloride is 1:1 to 1:3, preferably 1:2.1;
[0015] Preferably, the volume fraction of polydimethyldiallylammonium chloride in the polydimethyldiallylammonium chloride aqueous solution is 2%;
[0016] (3) adding the MXene obtained in step (1) and the PDDA@PA6S obtained in step (2) into deionized water, mixing by ultrasonication under nitrogen atmosphere and room temperature, stirring for 4 to 6 hours, centrifuging, collecting the precipitate and drying it in vacuum to obtain MXene@PA6S;
[0017] MXene@PA6S is obtained by electrostatic self-assembly; the mass ratio of MXene to PDDA@PA6S is 1:2 to 1:3, preferably 1:3;
[0018] (4) blending the polymer with the MXene@PA6S solution obtained in step (3) in an organic solvent, exchanging the solvent by a water solidification method, and freeze-drying to obtain a composite foam;
[0019] The specific operation is as follows: polymer and MXene@PA6S are added to an organic solvent, the resulting organic mixture is ultrasonically mixed under N2 atmosphere and room temperature, and stirring is continued for 4 to 6 hours. The thoroughly blended solution is then poured into a mold and placed in non-flowing deionized water for 3 hours. After solidification, it is taken out and freeze-dried to obtain a composite foam.
[0020] The polymer is selected from thermoplastic polyurethane (TPU); the organic solvent is selected from DMF; preferably, the mass fraction of the polymer and MXene@PA6S in the organic mixed solution is 20%;
[0021] Based on the total mass of the composite foam, the mass proportion of MXene@PA6S is 5-20%, preferably 15%;
[0022] The freeze-drying temperature is -60 to -45°C and the time is 48 to 72 hours.
[0023] The technical principle of the present invention is described as follows:
[0024] On the one hand, the surface charge of PA6S is changed by PDDA and electrostatically self-assembled with MXene with opposite charge. PA6S exhibits negative charge on the surface of the material due to its amide group, while the surface of MXene etched by lithium fluoride is also negatively charged due to its abundant hydroxyl and fluorine groups. The two are difficult to combine due to electrostatic repulsion. Therefore, PA6S is modified by cationic surfactants to change its original surface charge, so that its surface is positively charged, so that it can electrostatically self-assemble with negatively charged MXene. The prepared MXene@PA6S effectively improves the overall absorption performance of the composite foam. The surface defects and functional groups of MXene produced by etching will generate dipoles under the action of electromagnetic fields to improve the dielectric loss capacity of the material. In addition, the nano-scale thickness of MXene prevents electromagnetic waves from being completely reflected before reaching the skin depth, so that electromagnetic waves can enter the sphere of MXene@PA6S and cause multiple reflection losses.
[0025] On the other hand, MXene@PA6S was introduced into the TPU skeleton through solution blending and a polyurethane electromagnetic shielding composite foam was prepared by water curing and freeze drying. Due to the excellent conductivity and isolation structure of MXene@PA6S and the pore structure of the composite foam, the overall composite foam has both good electromagnetic shielding performance and absorption power coefficient. From a macroscopic perspective, the pores increase the number of interfaces inside the material, so that electromagnetic waves can have multiple reflection losses between the pores and the skeleton to improve the material absorption performance; from a microscopic perspective, electromagnetic waves can have multiple reflection losses in the MXene@PA6S sphere. In addition, the porous structure expands the spacing of the internal skeleton, and the excellent resilience allows the internal composite foam to easily adjust the spacing of the skeleton through compression, thereby adjusting the degree of contact of the conductive network and tuning the electromagnetic shielding effectiveness.
[0026] The beneficial effects of the present invention are:
[0027] 1. Polyurethane composite foam can tune the electromagnetic shielding effectiveness by simply compressing and releasing pressure. Compared with other excitation response methods, pressure response causes less damage to the material, has a simple tuning method, and a faster tuning rate.
[0028] 2. A MXene@PA6S particle was designed from the microstructure. Through certain modification and electrostatic self-assembly process, small-sized MXene was coated on large-sized PA6S, showing different coating conditions and wave absorption mechanism from conventional MXene electrostatic self-assembly, with excellent conductivity and wave absorption performance, which can reduce the percolation threshold and reduce the environmental pollution caused by secondary reflection.
[0029] 3. From a technological perspective, compared with the vacuum impregnation composite method, introducing MXene@PA6S particles into the TPU skeleton through solution blending and water curing can reduce the contact area between the easily oxidized MXene and the air, which can effectively improve the working stability of the material.
[0030] 4. Overall, under the synergistic effect of MXene@PA6S particles, TPU and foam cells, electromagnetic waves can be reflected multiple times between the foam cells and the skeleton. The composite foam has excellent absorption performance due to the increase in propagation path, reflection loss caused by impedance difference and interface polarization loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : The shielding mechanism of the compressible and tunable high-absorption electromagnetic shielding polymer composite foam of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.
[0033] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The raw materials and composite materials of all embodiments are vacuum dried and freeze-dried under the same conditions. The stirring method is magnetic stirring. The waveguide test is the average electromagnetic shielding effectiveness of the composite material in the X-band (8.2GHz-12.4GHz).
[0034] The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.
[0035] The PA6S used in the examples was homemade in the laboratory, and the specific raw materials contained were as follows: caprolactam (industrial grade, BASF), sodium hydroxide (AR, Xilong Chemical Company), toluene diisocyanate (AR, Alfa Aesar Chemical Co., Ltd.), polyethylene glycol (Mn = 4000, Shanghai Aladdin Biochemical Co., Ltd.); the preparation method of PA6S refers to LIU Y, FU X, DUAN J, et al. Self-assembly morphology evolution of the polyamide 6 (PA6) component in the PA6 / polyethylene glycol system by in situ polymerization of ∈-caprolactammonomer [J]. Polymer International, 2018.
[0036] PDDA (20%, 600-900 cp, Shanghai BiDe Pharmaceutical Technology Co., Ltd.).
[0037] TPU (6065A, Covestro, Germany).
[0038] Ti3AlC2 (400 mesh, Forsman Technology Co., Ltd.).
[0039] Lithium fluoride (99.9%, Shandong Keyuan Biochemical Co., Ltd.).
[0040] Example 1
[0041] Prepare a composite foam with a ratio of MXene@PA6S:TPU=1:4, and perform vector network analysis test in an uncompressed state. First, prepare a single layer or few layers of MXene, weigh 0.5g of Ti3AlC2 and 0.75g of LiF. Add the above drugs to a mixed solution consisting of 7.5ml of concentrated hydrochloric acid and 2.5ml of deionized water. Stir at room temperature for 24h. Centrifuge the solution at 3500rpm for 5min after the reaction, pour out the supernatant, and wash the precipitate with deionized water until the pH of the supernatant is neutral. After freezing the obtained precipitate in a refrigerator for 12h, add 20ml of deionized water and ultrasonicate for 30min in a N2 atmosphere. Then centrifuge the solution at 7000rpm for 15min, pour the supernatant into a culture dish, and freeze it in a refrigerator for 24h. Put the frozen sample in a freeze dryer and dry it for 24h to obtain a single layer or few layers of MXene powder. Secondly, PDDA-modified PA6S was prepared. 0.5 g of PA6S was weighed and added to 50 ml of 2 vol% PDDA aqueous solution. After stirring at room temperature for 5 h, the solution after the reaction was centrifuged and washed with deionized water at 4500 rpm for 5 min, and repeated 3 times. The precipitate was dried in a vacuum oven at 60 ° C for 12 h to obtain PDDA@PA6S. After that, MXene@PA6S particles with a ratio of MXene: PDDA@PA6S = 1:3 were prepared, and 0.1 g of MXene and 0.3 g of PDDA@PA6S were weighed. The above sample was added to 50 ml of deionized water, ultrasonicated at room temperature and N2 atmosphere for 20 min, and then stirred for 5 h. After the solution after the reaction was centrifuged at 4500 rpm for 5 min, the supernatant was poured off, and the precipitate was dried in a vacuum oven at 60 ° C for 12 h to obtain MXene@PA6S powder. Finally, 0.25 g of MXene@PA6S and 1 g of TPU were weighed. The above drugs were added to 6.6 ml of DMF solvent, and after half an hour of ultrasonication at room temperature under N2 atmosphere, stirring was continued for 5 hours. The solution after the reaction was poured into a culture dish with an inner diameter of 30 mm, and solidified in non-flowing deionized water for 3 hours, and then put into a refrigerator for 12 hours. After the freezing was completed, it was freeze-dried at -60°C for 48 hours to obtain polyurethane composite foam. The electromagnetic shielding test was performed using a vector network analyzer, and the electromagnetic shielding related parameters are shown in Table 1.
[0042] Example 2
[0043] Prepare a composite foam with a ratio of MXene@PA6S:TPU=1:9, and perform vector network analysis test in an uncompressed state. First, prepare a single layer or few layers of MXene, weigh 0.5g of Ti3AlC2 and 0.75g of LiF. Add the above drugs to a mixed solution consisting of 7.5ml of concentrated hydrochloric acid and 2.5ml of deionized water. Stir at room temperature for 24h. Centrifuge the solution at 3500rpm for 5min after the reaction, pour out the supernatant, and wash the precipitate with deionized water until the pH of the supernatant is neutral. After freezing the obtained precipitate in a refrigerator for 12h, add 20ml of deionized water and ultrasonicate for 30min in a N2 atmosphere. Then centrifuge the solution at 7000rpm for 15min, pour the supernatant into a culture dish, and freeze it in a refrigerator for 24h. Put the frozen sample in a freeze dryer and dry it for 24h to obtain a single layer or few layers of MXene powder. Secondly, PDDA-modified PA6S was prepared. 0.5 g of PA6S was weighed and added to 50 ml of 2 vol% PDDA aqueous solution. After stirring at room temperature for 5 h, the solution after the reaction was centrifuged and washed with deionized water at 4500 rpm for 5 min, and repeated 3 times. The precipitate was dried in a vacuum oven at 60 ° C for 12 h to obtain PDDA@PA6S. After that, MXene@PA6S particles with a ratio of MXene: PDDA@PA6S = 1:3 were prepared, and 0.1 g of MXene and 0.3 g of PDDA@PA6S were weighed. The above sample was added to 50 ml of deionized water, ultrasonicated at room temperature and N2 atmosphere for 20 min, and then stirred for 5 h. After the solution after the reaction was centrifuged at 4500 rpm for 5 min, the supernatant was poured off, and the precipitate was dried in a vacuum oven at 60 ° C for 12 h to obtain MXene@PA6S powder. Finally, 0.125 g of MXene@PA6S and 1.125 g of TPU were weighed. The above drugs were added to 6.6 ml of DMF solvent, and after half an hour of ultrasonication at room temperature under N2 atmosphere, stirring was continued for 5 hours. The solution after the reaction was poured into a culture dish with an inner diameter of 30 mm, and solidified in non-flowing deionized water for 3 hours, and then put into a refrigerator for 12 hours. After the freezing was completed, it was freeze-dried at -60°C for 48 hours to obtain polyurethane composite foam. The electromagnetic shielding test was performed using a vector network analyzer, and the electromagnetic shielding related parameters are shown in Table 1.
[0044] Example 3
[0045] Prepare a composite foam with a ratio of MXene@PA6S:TPU=1:19, and perform vector network analysis test in an uncompressed state. First, prepare a single layer or few layers of MXene, weigh 0.5g of Ti3AlC2 and 0.75g of LiF. Add the above drugs to a mixed solution consisting of 7.5ml of concentrated hydrochloric acid and 2.5ml of deionized water. Stir at room temperature for 24h. Centrifuge the solution at 3500rpm for 5min after the reaction, pour out the supernatant, and wash the precipitate with deionized water until the pH of the supernatant is neutral. After freezing the obtained precipitate in a refrigerator for 12h, add 20ml of deionized water and ultrasonicate for 30min in a N2 atmosphere. Then centrifuge the solution at 7000rpm for 15min, pour the supernatant into a culture dish, and freeze it in a refrigerator for 24h. Put the frozen sample in a freeze dryer and dry it for 24h to obtain a single layer or few layers of MXene powder. Secondly, PDDA-modified PA6S was prepared. 0.5 g of PA6S was weighed and added to 50 ml of 2 vol% PDDA aqueous solution. After stirring at room temperature for 5 h, the solution after the reaction was centrifuged and washed with deionized water at 4500 rpm for 5 min, and repeated 3 times. The precipitate was dried in a vacuum oven at 60 ° C for 12 h to obtain PDDA@PA6S. After that, MXene@PA6S particles with a ratio of MXene: PDDA@PA6S = 1:3 were prepared, and 0.1 g of MXene and 0.3 g of PDDA@PA6S were weighed. The above sample was added to 50 ml of deionized water, ultrasonicated at room temperature and N2 atmosphere for 20 min, and then stirred for 5 h. After the solution after the reaction was centrifuged at 4500 rpm for 5 min, the supernatant was poured out, and the precipitate was dried in a vacuum oven at 60 ° C for 12 h to obtain MXene@PA6S powder. Finally, weigh 0.0625g of MXene@PA6S and 1.1875g of TPU. Add the above drugs to 6.6ml of DMF solvent, ultrasonicate for half an hour at room temperature under N2 atmosphere, and continue stirring for 5h. Pour the solution after the reaction into a culture dish with an inner diameter of 30mm, put it into non-flowing deionized water for curing for 3h, put it into the refrigerator for freezing for 12h, and freeze-dry it at -60℃ for 48h after freezing to obtain polyurethane composite foam. The electromagnetic shielding test was carried out using a vector network analyzer, and the electromagnetic shielding related parameters are shown in Table 1.
[0046] Comparative Example 1:
[0047] Prepare a composite foam with a ratio of MXene:TPU=1:4. First, prepare a single layer or few layers of MXene, weigh 0.5g of Ti3AlC2 and 0.75g of LiF. Add the above drugs to a mixed solution consisting of 7.5ml of concentrated hydrochloric acid and 2.5ml of deionized water. Stir at room temperature for 24h. Centrifuge the solution at 3500rpm for 5min after the reaction, pour out the supernatant, and wash the precipitate with deionized water until the pH of the supernatant is neutral. After freezing the obtained precipitate in a refrigerator for 12h, add 20ml of deionized water and ultrasonicate for 30min under N2 atmosphere. Then centrifuge the solution at 7000rpm for 15min, pour the supernatant into a culture dish, and freeze it in a refrigerator for 24h. Put the frozen sample into a freeze dryer and dry it for 24h to obtain a single layer or few layers of MXene powder. Finally, weigh 0.25g of MXene and 1g of TPU. The above drugs were added to 6.6 ml of DMF solvent, and after half an hour of ultrasonication at room temperature under N2 atmosphere, stirring was continued for 5 hours. The solution after the reaction was poured into a culture dish with an inner diameter of 30 mm, and solidified in non-flowing deionized water for 3 hours, and then put into a refrigerator for 12 hours. After the freezing was completed, it was freeze-dried at -60°C for 48 hours to obtain polyurethane composite foam. The electromagnetic shielding test was performed using a vector network analyzer, and the electromagnetic shielding related parameters are shown in Table 1.
[0048] Comparative Example 2:
[0049] A composite foam with a ratio of MXene@PA6S:TPU=1:4 was prepared, and a vector network analysis test was performed under a compressive strain of 20%. The specific steps were the same as in Example 1.
[0050] Comparative Example 3:
[0051] A composite foam with a ratio of MXene@PA6S:TPU=1:4 was prepared, and a vector network analysis test was performed under a compression strain of 50%. The specific steps were the same as in Example 1.
[0052] Table 1
[0053] Total electromagnetic shielding effectiveness (dB) Absorption coefficient Example 1 38.42 0.61 Example 2 29.81 0.71 Example 3 8.24 0.19 Comparative Example 1 11.19 0.29 Comparative Example 2 24.41 0.55 Comparative Example 3 52.20 0.31
[0054] Compared with Examples 1, 2, and 3, the mass fraction of MXene@PA6S in the composite material decreases from 20wt% to 5wt%, and the electromagnetic shielding effectiveness and absorption coefficient of the composite material show a downward trend. Because MXene@PA6S with a core-shell structure isolates the conductive particles from the periphery of the PA6 microspheres. On the one hand, the synergistic effect of MXene@PA6S and the pores effectively reduces the percolation threshold of the composite material, which is more conducive to the construction of a conductive network. The more perfect the conductive network has better conductivity, which is a key factor affecting the electromagnetic shielding effectiveness; on the other hand, the structure is conducive to multiple reflection losses of electromagnetic waves inside the PA6 microspheres, converting energy into heat energy under interface polarization, thereby increasing the absorption coefficient. This also explains that in Example 1 and Comparative Example 1, at the same addition content, MXene@PA6S / TPU has better electromagnetic shielding effectiveness and absorption coefficient than MXene / TPU.
[0055] In the composite material, MXene@PA6S is mainly loaded on the TPU skeleton and the pore wall. The pore structure is conducive to increasing the multiple reflection loss, and it will also cause the conductive particles to be separated by the pores, resulting in an uneven conductive network. Therefore, by comparing Example 1 with Comparative Example 2, it can be found that as the compression strain increases to 20%, the contact area of the conductive particles increases due to the compression of the pores to a certain extent, but the degree of decrease in the multiple reflection loss is greater than the effect of the conductivity improvement on the electromagnetic shielding effectiveness, thereby showing a decrease in electromagnetic shielding performance under 20% compression strain. However, as the strain continues to increase, the impact of the integrity of the conductive network on the electromagnetic shielding effectiveness gradually exceeds the decrease in the multiple reflection loss, which explains the significant improvement in the electromagnetic shielding effectiveness under 50% strain in Comparative Example 3. At the same time, as the degree of pore compression increases, the internal multiple reflection loss decreases, which affects the absorption performance of the material. In addition, due to the increase in the conductivity of the composite material, the impedance difference increases, the proportion of the reflection coefficient increases, and the absorption coefficient shows a downward trend.
[0056] The present invention is described in detail with reference to specific examples, but the present invention is not limited to the above-mentioned embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention shall be considered as equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam, characterized in that: The following steps are involved: (1) Etching the MAX phase precursor using lithium fluoride and concentrated hydrochloric acid to obtain a single layer or a few layers of MXene; (2) adding nylon microspheres to a polydimethyldiallyl ammonium chloride aqueous solution, stirring at room temperature for 4 to 6 hours, then centrifuging and washing, collecting the precipitate and vacuum drying to obtain PDDA@PA6S; (3) adding the MXene obtained in step (1) and the PDDA@PA6S obtained in step (2) into deionized water, mixing by ultrasonication under nitrogen atmosphere and room temperature, stirring for 4 to 6 hours, centrifuging, collecting the precipitate and drying it in vacuum to obtain MXene@PA6S; (4) The polymer is blended with the MXene@PA6S solution obtained in step (3) in an organic solvent, and then the solvent is exchanged by a water solidification method and freeze-dried to obtain a composite foam.
2. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 1, characterized in that: Step (1) is as follows: MAX phase precursor, lithium fluoride, concentrated hydrochloric acid and deionized water are mixed, stirred at 30-40°C for 18-30h, then centrifuged at 3500rpm for 5min, the precipitate is washed with deionized water until the pH of the supernatant is neutral, the precipitate is collected and frozen, deionized water is added, ultrasonicated for 30min under N2 atmosphere, then centrifuged at 7000rpm for 15min, the supernatant is freeze-dried to obtain a single layer or few layers of MXene; The MAX phase precursor is Ti3AlC2; Concentrated hydrochloric acid is 12 mol / L.
3. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 2, characterized in that: The molar ratio of lithium fluoride to concentrated hydrochloric acid is 1:3 to 1:
3.
4. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 1, characterized in that: In step (2), the particle size of the nylon microspheres is 2 to 10 microns.
5. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 1, characterized in that: In step (2), the mass ratio of nylon microspheres to polydimethyldiallylammonium chloride is 1:1 to 1:
3.
6. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 1, characterized in that: In step (2), the volume fraction of polydimethyldiallylammonium chloride in the polydimethyldiallylammonium chloride aqueous solution is 2%.
7. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 1, characterized in that: In step (3), the mass ratio of MXene to PDDA@PA6S is 1:2 to 1:
3.
8. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 1, characterized in that: The operation of step (4) is as follows: adding the polymer and MXene@PA6S to the organic solvent, ultrasonically mixing the obtained organic mixture under N2 atmosphere and room temperature, and continuing to stir for 4 to 6 hours, then pouring the thoroughly blended solution into a mold, and placing it in non-flowing deionized water for 3 hours, and taking it out and freeze-drying it after solidification to obtain a composite foam; The polymer is selected from thermoplastic polyurethane; The organic solvent is selected from DMF.
9. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 8, characterized in that: The total mass fraction of polymer and MXene@PA6S in the organic mixed solution is 20%.
10. The method for preparing the compressible and tunable high-absorption porous polyurethane electromagnetic shielding composite foam as claimed in claim 8, characterized in that: Based on the total mass of the composite foam, MXene@PA6S accounts for 5 to 20% by mass.
Citation Information
Patent Citations
Electromagnetic shielding composite material with temperature response characteristic and preparation method and application thereof
CN115322442A
Preparation method of isolated thermoplastic elastomer composite microporous electromagnetic shielding material
CN111592684A
Integrated impedance gradient flexible wave-absorbing material and preparation method thereof
CN112538761A
Wave-absorbing polyamide composite material and preparation method thereof
CN114316577A
Preparation method of electromagnetic shielding PBS / PA6 green composite foam material
CN118108975A